(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The contemporaneity is marked by intense transformations that began in the Industrial Revolution of England in the 18th century and continues until the present moment, identified as the Fourth Phase of the Industrial Revolution that is responsible for affecting several characteristics of the production process. These changes will be responsible for changing the economic, commercial, social, environmental, technological and educational dimensions. In this context, we can understand the creation of different platforms within the educational environment. Thus, in this universe of hyperconnection, we increasingly interact with platforms that are responsible for helping us organize daily tasks. Faced with all these changes brought about by the modern world, this work aims to analyze and characterize the interactions and modifications performed by the teacher user in the Virtual Learning Environment (VLE), PVANet.